Social risks accounting for business valuation according to the VBM-approach - КоваленкоАлександр Александрович; ПаршиковДмитрий Михайлович (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2015)
Alexander Aleksandrovich Kovalenko - The individual businessman. E-mail: akovalenko777@mail.ru Dmitry Mikhailovich Parshikov - ZAO 2K Audit - Business Consulting. Senior Methodologist of the Department of Methodology and Quality Control of the Department of Evaluation, Expertise and Value Consultation. Email: homme65@inbox.ru The article deals with the development of social risk assessment methodology in the framework of Value Based Management. We believe that dedicated social risks significantly affect the future state of the organization, its potential and therefore must be taken into account in the calculation of the financial metrics. We propose a type of technology to measure social risks and their contribution to the discount rate by using build up method. The proposed method allows incorporating non-financial indicator – the value of social risk, based on expert’s estimates, into the discount rate. Therefore, it allows capturing the link between social risks and the goals of the organization.Our method can be used for the evaluation of various projects, justifying the calculation of the discount rate used in value-based analytics in the company.